The Experience of a Single Tertiary Center Regarding Benign and Malignant Tumors in Acromegalic Patients - Iulia-Stefania Plotuna; Melania Balas; Ioana Golu; Daniela Amzar; Adrian Vlad; Lavinia Cristina Moleriu; Mihaela Vlad (Medicina, 2023)
Background and Objectives: Acromegaly is a rare disease associated with increased levels of growth hormones (GHs) that stimulates the hepatic production of insulin growth factor-1 (IGF-1). Increased secretion of both GH and IGF-1 activates pathways, such as Janus kinase 2/signal transducer and activator of transcription 5 (JAK2/STAT5), and mitogen-activated protein kinase (MAPK), involved in the development of tumors. Materials and Methods: Given the disputed nature of the topic, we decided to study the prevalence of benign and malignant tumors in our cohort of acromegalic patients. In addition, we aimed to identify risk factors or laboratory parameters associated with the occurrence of tumors in these patients. Results: The study group included 34 patients (9 men (25.7%) and 25 women (74.3%)). No clear relationship between the levels of IGF-1 or GH and tumor development could be demonstrated, but certain risk factors, such as diabetes mellitus (DM) and obesity, were more frequent in patients with tumors. In total, 34 benign tumoral proliferations were identified, the most common being multinodular goiter. Malignant tumors were present only in women (14.70%) and the most frequent type was thyroid carcinoma. Conclusions: DM and obesity might be associated with tumoral proliferation in patients with acromegaly, and findings also present in the general population. In our study we did not find a direct link between acromegaly and tumoral proliferations.